From river to shelf, anatomy of a high‐frequency depositional sequence: The Late Pleistocene to Holocene Tiber depositional sequence. Issue 7 (10th June 2016) - Milli, Salvatore; Mancini, Marco; Moscatelli, Massimiliano; Stigliano, Francesco; Marini, Mattia; Cavinato, Gian Paolo
Abstract: The Late Pleistocene/Holocene Tiber delta succession represents the most recent and one of the best preserved, high‐frequency/low‐rank depositional sequences developed along the Latium continental margin of the Italian peninsula. Several previous studies have established a robust data set from which it has been possible to describe the stratigraphic architecture of the entire Tiber depositional sequence from the landward to seaward sectors and over a distance of 60 km. The Tiber depositional sequence shows many characteristics found in other Late Pleistocene to Holocene deltaic and coastal successions of the Mediterranean area. The stratigraphic architecture of the Tiber depositional sequence is controlled mainly by glacioeustasy, although factors such as tectonic uplift, volcanism and subsidence, exert an influence at a local scale. The resulting depositional model allowed discussion of some important points such as: (1) the genesis of the Tiber mixed bedrock‐alluvial valley, extending from the coastal plain to the innermost portion of the shelf, recording (i) multiple episodes of incision during relative sea‐level fall, and (ii) a downstream increase of depth and width of the valley during the base‐level fall and the subsequent base‐level rise; (2) the different physical expression of the Tiber depositional sequence boundary from landward to seaward, and its diachronous and composite character; (3) the maximum depth reached by the Tiber early lowstand delta at the end of the sea‐level fall is estimated at ca 90 m below the present sea‐level and not at 120 m as suggested by previous works; (4) the backward position of the Tiber late lowstand delta relative to the deposit of early lowstand; (5) the change of the channel pattern and of the stacking pattern of fluvial deposits within the Lowstand Systems Tract, Transgressive Systems Tract and Highstand Systems Tract. All of these features indicate that the Late Pleistocene/Holocene Tiber delta succession, even if deposited in a short period of time from a geological point of view, represents the result of the close interaction among many autogenic and allogenic factors. However, global eustatic variations and sediment supply under the control of climatic changes can be considered the main factors responsible for the stratigraphic architecture of this sedimentary succession, which has been heavily modified by human activity only in the last 3000 years.